X-ray computed tomography of multiple-layered scaffolds with controlled gradient cell lattice structures fabricated via additive manufacturing; Journal of Physics: Conference Series; Vol. 1145 : Prospects of Fundamental Sciences Development (PFSD-2018) - Khrapov D. Dmitriy; Surmeneva M. A. Maria Alexandrovna; Koptioug A.; Evsevleev S.; Léonard F.; Bruno G.; Surmenev R. A. Roman Anatolievich (2019, 2019)
Title screen